Consumer Perception of Global vs. Local Brands: The Indian Car Industry - Mathan Sankar, Shyamala (2006)
This study examines consumer perception of global brands vs. local brands in the Indian car industry. Consumer brand perceptions have substantial implications in Marketing. The study explores and understands consumer perceptions of global and local car brands in India by accomplishing the secondary objectives. The secondary objectives were achieved by highlighting the factors that effect consumer preference for global brands; by examining the effects of country of origin on consumer perceptions of global brands and local brands; and by studying the effects of consumer ethnocentrism towards global brands.